PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PENDEKATAN TEACHING AT THE RIGHT LEVEL - Ristiyaningtiyas, Ariskha; Purwati, Heni; Khasanah, Umi; Sugiyanti, Sugiyanti (STKIP PGRI Situbondo, 2024)
This study aims to improve students' Mathematical Problem Solving Ability (KPMM) through the application of learning with the TaRL approach and the Problem Based Learning (PBL) model. This research uses the type of Classroom Action Research (PTK) with two cycles. The subjects of this study were students of class XI-11 SMA Negeri 2 Semarang in the academic year 2023/2024. The research process was carried out by implementing learning in groups according to the level of students' cognitive abilities and given contextual problems. One class was divided into 9 groups according to the results of the diagnostic assessment that had been analysed. Groups 1-2 consists of students who have high ability can solve problems independently, groups 3-5 have moderate ability, given problems with a little scaffolding. Meanwhile, groups 6-9 have low abilities, in solving problems there are, given guidance and more intensive scaffolding. The data collection instruments used in this study were observation sheets of teacher activities, student activities, and KPMM tests. Based on the results of this study, it was found that there was an increase in mathematical problem solving ability on annuity material for students of class XI-11 SMA Negeri 2 Semarang. This is shown by the data on the increase in the number of students who have mathematical problem solving skills at least in the good category from 52.78% at the pre-cycle stage, increased to 66.67% in the first cycle,, then increasing again to 86.66% in the second cycle. The average score of students' problem solving ability also increased, from 72.98 in the pre-cycle to 77.53 in the first cycle, and reached 90.53 in the second cycle.